PENGARUH INQUIRY TRAINING BERBASIS EKSPERIMEN RIIL DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIS - Suriadi, Muhammad Fadli; Sinulingga, Karya (JURNAL IKATAN ALUMNI FISIKA, 2016)
This study aims to determine the effect of Inquiry Training learning model based real experiment and Critical Thinking Approach toward studentâs learning outcomes in the subject matter of Static Fluid of class X MAN 1 Stabat T.P. 2015/2016. This study was quasi experiment. Sampling was done by cluster random sampling, with a sample of two classes, class X-3 as an experimental class and class X-1 as an convensional class. The instrument used to determine student learning outcomes are result test in the form of 15 multiple-choice questions with 5 options, and the instrument used to critical thinking approach is 10 essay tests that have been validated by the validator. The data obtained are the result of pretest, posttest, and critical thingking approach test. Furthermore, the data is analyzed statistically consisting of normality test, homogeneity, hypothesis testing and ANAVA two ways. The results showed that: 1) there was an effect of Inquiry Training learning model based real experiment toward studentâs learning outcomes, 2) there was an effect of high crtitcal thinking and low critical thinking toward studentâs learning outcomes, 3) the effect of Inquiry Training learning model based real experiment and Critical Thinking Approach toward studentâs learning outcomes of class X MAN 1 Stabat T.P. 2015/2016.